Dampak Pandemi Covid-19 Terhadap Perkembangan Event E-Sports di Indonesia - Naomi Michelle Lim; Budi Setiawan (STIEPAR YAPARI Bandung, 2022)
Electronic sports (e-sports) is a competitive online game activity which has been approved as a sport by the Olympic Council of Asia (OCA) since 2017. The great interest of the world community, especially young people in e-sports, has made the industry developed into sports tourism and entertainment with the concept of digital tourism, organized in the form of national and international scale events. The Covid-19 pandemic has hampered various tourist activities, including e-sports events around the world. The design of this research is a qualitative descriptive literature review through case studies of e-sports events associated with the COVID-19 pandemic in Indonesia. The results of the study show that the COVID-19 pandemic followed by a large-scale social restriction has encouraged adaptation in the e-sports industry through the implementation of online e-sports events (streaming) which has an impact on the success of this industry to survive and even grow into a creative industry sub-sector that is proven to be able to thrive during the COVID-19 pandemic. The increase in the market ranking of the Indonesian e-sports industry from 16th in Southeast Asia in 2017 to the largest in Asia Pacific, and even 12th in the world in 2020 has shown the great potential of the e-sports event creative industry to move the wheels of the tourism industry which was on the ground during the COVID-19 pandemic in Indonesia.